Islamic Extremism : Causes, Diversity & Challenges - Palmer, Monte and Palmer, Princess (Dehli Foundation Books, 2011)
This accessible and deeply informed book examines the threat that Islamic extremists pose to America and provides a balanced and nuanced discussion of the link between Iraq and the war on terror. Explaining the basics of Islam and guiding the reader through the intricacies of each significant fundamentalist group, the Palmers answer key questions: Who are the Muslim extremists and how do they fit within the broader context of the Islamic religion? What is their war plan and how do they operate? Who are their allies and what are their weaknesses? What is the experience of Israel, the Islamic world, and the United States in fighting Muslim extremists? How can they be defeated? The book includes detailed analyses of Hizbullah and the Muslim Brotherhood, Hamas, the Iraqi clones of Hizbullah, and the Islamic government in Turkey.
Includes Index
Keywords: War on Terrorism (2001-2009)